2021
DOI: 10.1038/s41467-020-20291-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient carbon dioxide hydrogenation to formic acid with buffering ionic liquids

Abstract: The efficient transformation of CO2 into chemicals and fuels is a key challenge for the decarbonisation of the synthetic production chain. Formic acid (FA) represents the first product of CO2 hydrogenation and can be a precursor of higher added value products or employed as a hydrogen storage vector. Bases are typically required to overcome thermodynamic barriers in the synthesis of FA, generating waste and requiring post-processing of the formate salts. The employment of buffers can overcome these limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 49 publications
0
64
0
Order By: Relevance
“…Obviously, the hydrogenation of CO 2 in basic aqueous solution is more feasible thermodynamically. However, in most cases of CO 2 hydrogenation, harsh conditions including high temperature, high pressure, and the use of organic solvents as well as catalyst are still required. , Although homogeneous catalysts based on Ru, Ir, Co, Fe, and so on , have been extensively investigated, reports of metal complexes under ambient conditions are still quite rare. For example, for Cp*Ir complexes (Scheme ), [Cp*Ir­(4-(1 H -pyrazol-1-yl-κN 2 )­benzoic acid-κC 3 )­(H 2 O)] 2 ­SO 4 reported by Fukuzumi and [Cp*Ir­(dhbp)­(H 2 O)]­SO 4 (dhbp = 4,4′-di­hydroxy-2,2′-bipyridine) reported by Fujita achieved respective 6.8 and 70 h –1 TOFs for CO 2 hydrogenation to produce formate under atmospheric pressure (CO 2 /H 2 = 0.05 MPa/0.05 MPa) at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the hydrogenation of CO 2 in basic aqueous solution is more feasible thermodynamically. However, in most cases of CO 2 hydrogenation, harsh conditions including high temperature, high pressure, and the use of organic solvents as well as catalyst are still required. , Although homogeneous catalysts based on Ru, Ir, Co, Fe, and so on , have been extensively investigated, reports of metal complexes under ambient conditions are still quite rare. For example, for Cp*Ir complexes (Scheme ), [Cp*Ir­(4-(1 H -pyrazol-1-yl-κN 2 )­benzoic acid-κC 3 )­(H 2 O)] 2 ­SO 4 reported by Fukuzumi and [Cp*Ir­(dhbp)­(H 2 O)]­SO 4 (dhbp = 4,4′-di­hydroxy-2,2′-bipyridine) reported by Fujita achieved respective 6.8 and 70 h –1 TOFs for CO 2 hydrogenation to produce formate under atmospheric pressure (CO 2 /H 2 = 0.05 MPa/0.05 MPa) at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the expected thermodynamic behavior of the system as well as recent reports detailing this reaction. 48 Examining the kinetics of bicarbonate hydrogenation we found that 1 is capable of developing high turnover frequencies (TOFs) with no apparent inhibition often observed in organic media. 49 Tracking hydrogen consumption in the course of hydrogenation we estimated the initial TOF to be in the extent of 73 000 h −1 (Fig.…”
mentioning
confidence: 91%
“…This is consistent with expected thermodynamic behavior of the system as well as recent reports detailing this reaction. [12] Examining kinetics of bicarbonate hydrogenation we found that 1 is capable of developing high turnover frequencies (TOF) with no apparent inhibition often observed in organic media. [13] Tracking hydrogen consumption in the course of hydrogenation we estimated initial TOF in extent of 73 000 h -1 (Figure 4) with kinetic traces following a regular monoexponential trendline.…”
mentioning
confidence: 91%